"Sad day for the UK": The linking of debates about settling refugee children in the UK with Brexit on an anti‐immigrant news website. (18th April 2019) - Goodman, Simon; Narang, Amrita
Abstract: This article uniquely demonstrates how UK debates about supporting child refugees during the "refugee crisis" came to be used as support for leaving the European Union (EU). The research question "how did users of a news website respond to a report about the UK government's decision to allow child refugees into the UK?" is addressed with a rigorous discursive analysis of an internet discussion forum on the anti‐immigrant website MailOnline consisting of 2, 014 unique posts, with a reach of 30 million viewers. Analysis demonstrated that (1) child refugees were presented as adults, (2) allowing in refugees was presented as a "burden" on taxpayers, (3) the decision was presented as opposed to the public's will, and (4) this was used as a warrant for leaving the EU. The significant implication of this analysis is that political attempts at associating the refugee crisis with the EU may have been successful in this context.